Biokimia Etnofarmasi Aplikasi dalam Kehidupan Masyarakat Suku Anak Dalam - Nayla Fazila Nadin; Ardi Mustakim (Lembaga Pengembangan Kinerja Dosen, 2026)
Ethnopharmacy is a field of study that examines traditional medicinal practices based on local knowledge along with their underlying biochemical foundations, and it is increasingly recognized for its role in preserving local wisdom while contributing to the development of modern healthcare solutions. Among the Suku Anak Dalam community, the use of medicinal plants has been practiced for generations as a means of preventing and treating various diseases, reflecting a deep empirical understanding of the therapeutic properties of natural remedies available in their surrounding environment. This study aims to examine the biochemical basis of ethnopharmaceutical practices applied by the Suku Anak Dalam community and to analyze their application in daily life. Data were collected through direct field observations, structured interviews with community members knowledgeable about traditional medicine, and literature reviews related to the bioactive compound content of the most commonly used medicinal plants. The results indicate that many of the plants utilized contain active compounds with anti-inflammatory, antimicrobial, and antioxidant properties, which play an important role in supporting community health. These findings highlight the complexity and scientific value of traditional knowledge and emphasize the importance of integrating ethnopharmaceutical practices with modern biochemical research to develop natural medicines, preserve cultural heritage, and sustainably improve public health quality.